РУССКИЕ СУБСТАНТИВНЫЕ ОМОГРАФЫ - Kaliszan, Jerzy (Studia Rossica Posnaniensia, 2008)
In the article the Russian substantival homographs such as атлас - атлас, замок - замок, отзыв - отзыв are analysed. The author examines the main factors and mechanisms of their formation. He comes to a conclusion that the overwhelming majority of them (about 70%) can be considered as a result of derivational (word formative) processes.